The Directive 2014/24/EU and the implementation of e-procurement in Portugal – part I - Carvalho, Raquel (2019)
Portugal has been leading the way in the implementation of e-procurement within the European Union. This paper, presented in two Parts, starts, in this Part I, by explaining the framework of e-procurement, describing the Portuguese experience regarding the use of electronic platforms based on factual data assembled by the Portuguese regulatory body. Part II describes the legal regime imposed by the European Union Law thoroughly, particularly by article 22 of Directive 2014/24/EU, which is contained in a specific ruling as it has occurred before the full 2014 Directives transposition. To provide the full picture of e-procurement in Portugal, the paper also explains the projected intention of the Directive transposition and the actual legal ruling enshrined in the Public Contracts Code (PCC).